2018
DOI: 10.1021/acsomega.8b00401
|View full text |Cite
|
Sign up to set email alerts
|

A New Methodology for Evaluating the Structural Similarity between Different Phases Using a Dimensionality Reduction Technique

Abstract: A new methodology for definitively evaluating the structural similarity between different phases in an impartial manner is proposed. This methodology utilizes a dimensionality reduction (DR) technique that was developed in the fields of machine learning and statistics. The basis of the proposed methodology is that the structural similarity between different phases can be evaluated by the geometrical similarity of pair and/or angular distribution functions that reflect the atomic-scale structure of each phase. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 49 publications
(190 reference statements)
0
9
0
1
Order By: Relevance
“…The structural similarity among different periods was evaluated by the distance between the 2D data points on the sheet; the shorter the distance was, the higher the similarity. In a previous study 16 , it was confirmed that the transformation of the PDF and ADF geometries into 2D data points with PCA provided qualitatively the same results as the transformation of them into three-dimensional data points with PCA. This result of the previous study suggests that the exactness of the features of the PDF and ADF geometries represented by 2D data points with PCA is sufficiently high.…”
Section: Resultsmentioning
confidence: 53%
See 4 more Smart Citations
“…The structural similarity among different periods was evaluated by the distance between the 2D data points on the sheet; the shorter the distance was, the higher the similarity. In a previous study 16 , it was confirmed that the transformation of the PDF and ADF geometries into 2D data points with PCA provided qualitatively the same results as the transformation of them into three-dimensional data points with PCA. This result of the previous study suggests that the exactness of the features of the PDF and ADF geometries represented by 2D data points with PCA is sufficiently high.…”
Section: Resultsmentioning
confidence: 53%
“…So far, DR has been used to evaluate geometrical similarities or dissimilarities between different objects, such as surface recognition 22 , face recognition 23 , and surface matching 24 , in which DR was performed for high-dimensional data representing the geometry of each object. Recently, DR was used to evaluate the geometrical similarity of the PDF and ADF between different phases of calcium carbonate, and the results represented the structural similarity among those phases in real systems 16 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations